NAMA-NAMA TEMPAT MAKAN KHAS MINANGKABAU DI KOTAMADYA BUKITTINGGI - Sandra Mulyana Rahmat (Universitas Andalas, 2017)
This paper describes the meaning of the eatery names in Bukittinggi. Data provide with simak method. The basic technique is sadap and the advanced technique is simak libat cakap technique and simak bebas libat cakap technique continued with an interview. Data were analyzed with padan technique.The results show that the names of eatery in the Bukittinggi have different meanings, namely based on the background of owner origin, the unique characteristic, similarity, and an abbreviation. The use of these meanings can be classified in the form of lexical and referential meanings.